Development and implementation of social work practice learning opportunities in NHS settings with no previous experience of social work education - Hughes, Marianne (The Journal of Practice Teaching and Learning, 2012)
The purpose of this paper is to outline the knowledge and practice used at a strategic, organisational and practice level in the planning and implementation of effective social work practice learning opportunities in NHS settings new to direct social work practice and social work education. The paper outlines the process which was used in order to create new interprofessional practice learning opportunities and it is intended to add to ‘process knowledge’ (Sheppard et al., 2000). Additionally the paper draws on the content of the ‘matrix of drivers and barriers to integrated working’ developed for the area of interprofessional practice (Stewart, Petch, & Curtice, 2003) and transfers this knowledge as applicable to Social Work education. In practice, across human services, there continues to be views of ‘other’ professional groups that can create obstacles to the development and maintenance of positive inter-professional working, and that can undermine effective service delivery for service users (Report of Caleb Ness Inquiry, 2003). The experience of inter-professional practice learning, when combined with emotional intelligence (Morrison, 2007) can impact positively to increase the confidence, knowledge-base and direct inter-professional practice of newly qualifying Social Workers.